2010
DOI: 10.1161/circresaha.110.216770
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Asymmetric Dimethylarginine Impairs Angiogenic Progenitor Cell Function in Patients With Coronary Artery Disease Through a MicroRNA-21–Dependent Mechanism

Abstract: Rationale: The endogenous nitric oxide synthase inhibitor asymmetrical dimethylarginine (ADMA) is increased in patients with coronary artery disease and may regulate function of circulating angiogenic progenitor cells (APCs) by small regulatory RNAs. Objectives: To study the role of microRNAs in ADMA-mediated impairment of APCs. Methods and Results: By using microarray analyses, we established microRNA expression profiles of human APCs.We used ADMA to induce APC dysfunction and found 16 deregulated microRNAs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
107
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(117 citation statements)
references
References 21 publications
8
107
0
2
Order By: Relevance
“…6 However, cardiovascular risk factors and aging were shown to impair the functions of this endogenous pool of proangiogenic cells. 84,85 The functional impairment of these cells in patients with coronary artery disease was associated with an increased expression of miR-21 86 and a dysregulation of other vascular miRs. 87 Interestingly, antagonizing miR-21 led to an improved functionality of proangiogenic cells from patients with coronary artery disease who otherwise experienced oxidative stress mediated by an upregulation of miR-21 in this disease state.…”
Section: Mirs In Adult Progenitor Cellsmentioning
confidence: 99%
“…6 However, cardiovascular risk factors and aging were shown to impair the functions of this endogenous pool of proangiogenic cells. 84,85 The functional impairment of these cells in patients with coronary artery disease was associated with an increased expression of miR-21 86 and a dysregulation of other vascular miRs. 87 Interestingly, antagonizing miR-21 led to an improved functionality of proangiogenic cells from patients with coronary artery disease who otherwise experienced oxidative stress mediated by an upregulation of miR-21 in this disease state.…”
Section: Mirs In Adult Progenitor Cellsmentioning
confidence: 99%
“…Villeneuve et al (38,39) found that miR-125b may increase the expression of inflammatory genes in vascular endothelial cells to cause endothelial dysfunction. Weber et al (40) and Fleissner et al (41) also found that miR-21 was able to reduce the rate of apoptosis in vascular endothelial cells and promote the release of nitric oxide to protect the vascular endothelium. Caporali et al (42) reported that inhibition of miR-15 improved endothelial function in culture conditions mimicking diabetes mellitus (high D-glucose), and CCNE1 and CDC25A were direct miR-15 targets.…”
Section: Discussionmentioning
confidence: 99%
“…[36] Together with other studies, which show an impairment of migration and angiogenic capacity of adult bone marrow-derived mononuclear cells, [66,67] this might contribute to the limited capacity of BM-MNCs in clinical trials to effectively impact on cardiac function. In this respect a phase I trial was recently published using allogeneic bone marrow derived cells [68] from healthy donors as an off-the-shelf product, that may circumvene impairment of autologous cell function in patients with cardiovascular disease.…”
Section: Potential Impact Of Cell Isolation Procedures and Impaired Fmentioning
confidence: 92%